Concentrating Solar Power in Developing Countries : Regulatory and Financial Incentives for Scaling Up - Kulichenko, Natalia; Wirth, Jens (Washington, DC: World Bank, 2012)
Concentrating Solar Thermal power (CST) has a tremendous potential for scaling up renewable energy at the utility level, diversifying the generation portfolio mix, powering development, and mitigating climate change. At present, different CST technologies have reached varying degrees of commercial availability. This emerging nature of CST means that there are market and technical impediments to accelerating its acceptance, including cost competitiveness, an understanding of technology capability and limitations, intermittency, and benefits of electricity storage. Many developed and some developing countries are currently working to address these barriers in order to scale up CST-based power generation. This report: a) analyzes and draws lessons from the efforts of some developed countries and adapts them to the characteristics of developing economies; b) assesses the cost reduction potential and economic and financial affordability of various technologies in emerging markets; c) evaluates the potential for cost reduction and associated economic benefits derived from local manufacturing; and d) suggests ways to tailor bidding models and practices, bid selection criteria, and structures for power purchase agreements (PPAs) for CST projects in developing market conditions. The report also presents a review of typical cost structures for parabolic trough and power tower plants, which was derived from projects developed or under preparation in Spain and the United States specifically for this report, and an in-depth assessment of the respective cost drivers.